ANALISIS TEORITIK PROKRASTINASI AKADEMIK MAHASISWA - Syarifan Nurjan (MUADDIB Jurnal Kependidikan dan Keislaman, 2020)
Academic procrastination is the behavior of students who delay in completing academic assignments that have a bad effect with the tasks are increasingly piled up and abandoned, do not pay attention to deadlines of tasks that should be completed which have an impact on students' psychic and psychological. Academic procrastination is basically influenced by 2 factors: internal factors are related to individual disposition and external factors in the form of outside factors that come from psychosocial and environmental aspects.Theoretical analysis of student academic procrastination with an understanding of the understanding of academic procrastination, history of procrastination, characteristics of academic procrastination, factors of academic procrastination, measurement of academic procrastination, and academic procrastination of an Islamic perspective. A comprehensive understanding of academic procrastination will reduce the failure of students to carry out academic assignments and achieve outstanding academic achievement.